2015
DOI: 10.1021/acsnano.5b03157
|View full text |Cite
|
Sign up to set email alerts
|

Cells Sensing Mechanical Cues: Stiffness Influences the Lifetime of Cell–Extracellular Matrix Interactions by Affecting the Loading Rate

Abstract: The question of how cells sense substrate mechanical cues has gained increasing attention among biologists. By introducing contour-based data analysis to single-cell force spectroscopy, we identified a loading-rate threshold for the integrin α2β1-DGEA bond beyond which a dramatic increase in bond lifetime was observed. On the basis of mechanical cues (elasticity or topography), the effective spring constant of substrates k is mapped to the loading rate r under actomyosin pulling speed v, which, in turn, affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 55 publications
2
46
1
Order By: Relevance
“…The substrate elasticity determines the effective spring constant of substrates and the loading rate under actomyosin pulling speed on integrin α2β1-DGEA bond, which in turn affects the lifetime of the integrin ligand bond. (Jiang et al, 2015) The present work also showed that down regulating actomyosin pulling speed by a low dose blebbistatin treatment markedly enhanced internalization of both integrin 1 and 2, suggesting that not only integrin α2β1, but also integrin 1β1 is loading rate sensitive (Fig.S4). Thus the loading rate-stiffening property of the integrin is crucial for collagen-coated soft substrate promoting internalization.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The substrate elasticity determines the effective spring constant of substrates and the loading rate under actomyosin pulling speed on integrin α2β1-DGEA bond, which in turn affects the lifetime of the integrin ligand bond. (Jiang et al, 2015) The present work also showed that down regulating actomyosin pulling speed by a low dose blebbistatin treatment markedly enhanced internalization of both integrin 1 and 2, suggesting that not only integrin α2β1, but also integrin 1β1 is loading rate sensitive (Fig.S4). Thus the loading rate-stiffening property of the integrin is crucial for collagen-coated soft substrate promoting internalization.…”
Section: Discussionsupporting
confidence: 73%
“…(Du et al, 2011;Zu et al, 2015). Our more recent research shows a threshold of the loading rate on integrin α2β1-DGEA bond, the specific binding site of integrin α2β1 on collagen I, beyond which a dramatic increase of the bond lifetime was seen.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations